GROWTH AND CONDITION OF PINE PLANTATIONS, CREATED BY THE PLANTING MATERIAL GROWN USING PLANT GROWTH REGULATORS - Taranenko, Yu. M. (Forestry and Forest Melioration, 2018)
Introduction Artificial reforestation is impossible without enough amount of high quality planting material of forest species. Use of plant growth regulators (PGR) is one of the ways of improvement of planting material quality. Our previous research shows that use of PGR brings to increase the number of seedlings, their survival, linear dimensions and mass. It was important to study the aftereffect of PGR in the first years of plantation growing. Aim of research was to reveal the peculiarities of diameter, height and condition dynamics of pine plantations created by planting material, which was grown using plant growth regulators (PGR). Materials and Methods Seedlings of Scots pine (Pinus sylvestris L.) were grown in the Gogolivske forestry forest nursery of the State Enterprise “Myrgorodske Forest Economy” from seeds of 2009 year. These seeds before sowing were soaked for 18 hours in PGR solutions: Bajkal (10, 5 and 2.5 ml/l), Lignogumat (1, 0.5 and 0.05 ml/l), Tryman (1, 0.5 and 0.05 мл/л), Charkor (4, 2 and 1 ml/l) and Epin (4, 2 and 1 ml/l). In control, pine seeds were soaked in clean water for the same time interval. Obtained planting material was planted in spring 2010 in forest plot 42, subplot 1 of Gogolivske forestry of the State Enterprise “Myrgorodske Forest Economy”. Forest plantation was planted in the area after recent clear-cut in fresh relatively poor site conditions. Distance between plants was 0.5 m in the row and 2.5 m between rows. There were 15 variants using seedlings from PGR treated seeds and one control variant (1700 plants in total). Survival, condition, root collar diameter and height of plants were assessed in 2010 and 2011. Sanitary condition of plants was evaluated on a 4-point scale: 1 – excellent condition; 2 – good; 3 – satisfactory (weakened); 4 – very poor. Root collar diameter, height and height increment for each year were measured also in 2015. Data on air temperature and precipitation were taken from meteorological station Myrgorod. All data were analyzed using standard procedures of descriptive statistics, correlation analysis and ANOVA using MS Excel. Results and Conclusions Use of PGRs for Scots pine seeds treatment promoted good plant survival and growth in plantations during the early years. However, the growth of plantations also depended on external factors. Aftereffect of Scots pine seeds treatment continues in the early years of plantation growing and is manifested in the higher values of survival, height and condition of plants vs. control. There were no significant differences by these parameters between the variants with use different PGRs and their concentrations at seed treatment. In the year of transfer to the forest covered lands the plantations created with planting material, which was grown using PGRs, were evaluated as the 1st quality class, and control plantations were evaluated as 2nd quality class. The existence of reliable high positive correlation of pine plantation height growth in 2011–2015 with June air temperature and negative correlation with May and June precipitation, as well as with their sum are proved.